ChemInform Abstract: Rhodium‐Catalyzed Stereoselective Intramolecular [5 + 2] Cycloaddition of 3‐Acyloxy 1, 4‐Enyne and Alkene. Issue 9 (February 2016) - Shu, Xing‐zhong; Schienebeck, Casi M.; Li, Xiaoxun; Zhou, Xin; Song, Wangze; Chen, Lianqing; Guzei, Ilia A.; Tang, Weiping
Abstract: The alkyne moiety may be terminal or internal and the alkene moiety may be 1‐substituted, 1, 2‐disubstituted, but not trisubstituted.